The impact of the emergence of COVID‐19 on women's prenatal genetic testing decisions. (5th March 2021) - Farrell, Ruth M.; Pierce, Madelyn; Collart, Christina; Craighead, Caitlin; Coleridge, Marissa; Chien, Edward K.; Perni, Uma; Frankel, Richard; Ranzini, Angela; Edmonds, Brownsyne Tucker; Rose, Susannah S.
Abstract: Objective: We conducted a study to examine the impact of COVID on patients' access and utilization of prenatal genetic screens and diagnostic tests at the onset of the COVID‐19 pandemic in the United States. Methods: We conducted telephone interviews with 40 patients to examine how the pandemic affected prenatal genetic screening and diagnostic testing decisions during the initial months of the pandemic in the United States. An interview guide queried experiences with the ability to access information about prenatal genetic testing options and to utilize the tests when desired. Audio recordings were transcribed and coded using NVivo 12. Analysis was conducted using Grounded Theory. Results: The pandemic did not alter most participants' decisions to undergo prenatal genetic testing. Yet, it did impact how participants viewed the risks and benefits of testing and timing of testing. There was heightened anxiety among those who underwent testing, stemming from the risk of viral exposure and the fear of being alone if pregnancy loss or fetal abnormality was identified at the time of an ultrasound‐based procedure. Conclusion: The pandemic may impact patients' access and utilization of prenatal genetic tests. More research is needed to determine how best to meet pregnant patients' decision‐making needs during this time. Key Points: What is already known about this topic? Prenatal genetic screens and diagnostic tests are a core component to the delivery of high‐quality, evidence‐based prenatal care. It is critical that pregnant patients have the information and resources to make an informed decision about a growing array of prenatal genetic screening and diagnostic testing options. In the decision‐making process, pregnant patients commonly weigh the risks and benefits of gaining genetic information about the fetus with the risks and benefits of the available screens and diagnostic tests. What does this study add? The pandemic has led to significant changes in healthcare delivery and insurance benefits for prenatal genetic testing, raising key questions about how pregnant patient are weighing the risks and benefits of the available prenatal genetic screening and diagnostic testing options against the risks of COVID exposure by presenting to a healthcare facility for testing. COVID‐19 appears to impact how women view the utility of prenatal genetic testing, including how they weigh the risk and benefits of prenatal genetic screening and diagnostic testing in addition to when in the pregnancy they may elect to undergo testing. The COVID‐19 pandemic has resulted in increased levels of concern and anxiety that may be encountered by pregnant women in the testing process, raising awareness of the need for additional resources to support patients' decision‐making during the pandemic.